CAPITALISM, CONSUMERISM AND POPULAR CULTURE - Singh, Ankita (International Journal of Research -GRANTHAALAYAH, 2018)
A product’s utility has evolved over time. In today’s world, the commodities possess the power to define us. Every product that we own today, through its branding, reflects our social status, values and vice versa. It is difficult to refute the negative influence of capitalism that we witness in form of obsession with possession. The aim of the paper is to study the extent to which the products of the modern society like the protagonists in the following two movies suffer; whether it is possible to imagine an end of consumerism and not the world or has it become an inherent part of the late capitalist world in which there is no completeness but the perennial emergence of substitutes (objects). This paper studies the aforementioned issues through the movies “Fight Club” and “Confessions of a Shopaholic”. The first section of the paper uses the case of soap industry as the foundation and analyses “Fight Club”. The second section examines the role of credit card companies in compulsive buying disorder through “Confessions of a Shopaholic”. Despite the similarity between the two movies on the grounds of the modern world “suffering”, the paper highlights the difference in their treatment of the main theme of consumerism and links it to the gender politics. The final section draws a comparison between the endings of the two movies and investigates the premise of disorder in “Fight Club” and its existential threat to capitalism.